P421 Effects of combination therapy in inflammatory bowel disease: how long should we keep concomitant immunomodulators?. (25th January 2019) - Silva, J C; Silva, A P; Rodrigues, A; Fernandes, C; Ponte, A; Rodrigues, J; Sousa, M; Gomes, A C; Carvalho, J
Abstract: Background: Combination therapy (CT) in inflammatory bowel disease (IBD) is considered to be superior to monotherapy. Reduction of biological immunogenicity is believed to be an advantage, especially in the first 6 months. Nonetheless CT may increase the risk of neoplasia and infection. The aim of this study was to evaluate the benefits of CT beyond 6 months. Methods: Retrospective cohort-study, which included all IBD patients who underwent treatment with anti-TNF between 2003–2017 in our unit. Inclusion criteria: IBD patients submitted to CT (anti-TNF+immunomodulator) for at least 3 months. Patients who lost follow-up were excluded. Patients were divided in 2 groups, based on CT duration (≤6 months and >6 months). The main outcomes include time to biologic treatment failure (defined as need to dose increase, switch biologic or surgery) and immunomodulator-related adverse events. Long-term clinical remission (CR) as well as deep remission (DR) were the secondary outcomes. DR was defined as CR (as described in medical records), endoscopic remission (absence of ulcers and erosions in endoscopy) and in ileal Crohn's disease as absence of radiologic activity. Results: 136 patients were included, 90 of which underwent CT. Most patients had Crohn's disease (90%). Mean age was 38.3 years (SD 12.5) and 56% were females ( n = 50). Median duration of combined therapy was 12-months (IQR 6), and most patients maintained combination therapy after 6-months (84.4%, n = 76). Adverse reactions were attributed to immunomodulator in 7.8% ( n = 7), most of them (71.4%, n = 5) in the first 6-months of treatment. There was not a significant association between biologic treatment failure and duration of CT ( p = 0.396). Time to relapse was not correlated to the duration of CT ( p = 0.451). There was also no association between CT duration and need to escalate to a second ( p = 0.352) or third biologic ( p = 0.419). Longer CT was also not significantly associated with long-term clinical remission ( p = 0.804) nor deep remission ( p = 0.329). Conclusions: There was no additional benefit in maintaining combination therapy beyond 6 months. Considering the long-time risks, namely infections and neoplasia, it is reasonable to consider that combined therapy for 6-months may be as effective as concomitant therapy for longer periods.